2003
DOI: 10.2337/diabetes.52.11.2784
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Interleukin-6 Causes Hepatic Insulin Resistance in Mice

Abstract: Interleukin (IL)-6 is one of several proinflammatory cytokines associated with the insulin resistance of obesity and type 2 diabetes. There is, however, little direct evidence in vivo for a causative role of IL-6 in insulin resistance. Here, a 5-day constant subcutaneous infusion of hIL-6 before portal vein insulin challenge resulted in impairment of early insulin receptor signaling in the liver of mice. Importantly, the sixfold elevation of IL-6 attained with constant infusion was similar to levels reached in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
329
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(361 citation statements)
references
References 50 publications
19
329
0
13
Order By: Relevance
“…While the role of IL-6 in whole-body insulin resistance is unclear, it is generally accepted that excessive circulating IL-6 causes hepatic insulin resistance [30]. This conclusion is based on several observations demonstrating that exogenous administration of IL-6 impairs insulin signal transduction in the liver in vitro [36,37] and in vivo [13]. In addition, IL-6-neutralising antibodies have been shown to reverse hepatic insulin resistance in mice [38,39], while transient overproduction of IL-6 in skeletal muscle by in vivo electroporation resulted in liver inflammation [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the role of IL-6 in whole-body insulin resistance is unclear, it is generally accepted that excessive circulating IL-6 causes hepatic insulin resistance [30]. This conclusion is based on several observations demonstrating that exogenous administration of IL-6 impairs insulin signal transduction in the liver in vitro [36,37] and in vivo [13]. In addition, IL-6-neutralising antibodies have been shown to reverse hepatic insulin resistance in mice [38,39], while transient overproduction of IL-6 in skeletal muscle by in vivo electroporation resulted in liver inflammation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Acute IL-6 administration during a euglycaemic-hyperinsulinaemic clamp results in a glucose infusion rate that is either unchanged in rats [10,11], decreased in mice [12] or increased in humans [7]. Short-term (5 to 14 days), exogenous administration of IL-6 to lean rodents causes hepatic insulin resistance in mice [13], but increased wholebody insulin sensitivity and glucose tolerance in rats [14]. Recently, another team has demonstrated that human IL6 transgenic mice with sustained elevated circulating IL-6 display enhanced central leptin action and improved nutrient homeostasis leading to protection from dietinduced obesity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the role of IL-6 in whole body energy homeostasis remains partly contradictory. However, several experimental studies have shown that IL-6 impairs insulin sensitivity and action in rodent and human hepatocytes as well as inducing hepatic insulin resistance in vivo in mice [48][49][50]. This insulin desensitising effect in liver cells is, in part, the result of IL-6 inducing marked inflammation in this tissue [29].…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The inflammatory response of adipocytes upon infection may also have paracrine effects by affecting the function of neighboring adipocytes and may attract macrophages into adipose tissue, increasing the capacity for the production of inflammatory mediators. The production of the proinflammatory cytokines IL-6, TNF-a and monocyte chemotactic protein-1 (MCP-1) is upregulated in a co-culture with 3T3-L1 adipocytes and a macrophage cell line RAW264.…”
Section: Discussionmentioning
confidence: 99%